Effects of the menstrual cycle on fat utilization during 1 hour of cycling at fatmax - García-Ortiz, C.; Fernández-Sánchez, J.; García-Albín, D.; Ranieri, L. E.; Trujillo-Colmena, D.; Solano-Lizcano, V.; Rodríguez-Castaño, A.; Collado-Mateo, D.; Casado, A.; Del Coso, J. (International Journal of Sports Physiology and Performance, 2026)
Purpose: This study aimed to investigate fat utilization during 1 hour of cycling at maximal fat oxidation and, secondarily, to assess menstrual symptoms across different phases of the menstrual cycle.